Empowerment of social and cultural in the life of FELDA community - Abdullah, Azlina; Hassan, Nor Azlili; Ismail, Mohd Mahadee; Mak Din, Hairol Anuar; Md Yunus, Marzudi; Mohd Noor, Mansor (Pennwell Corporation, 2020)
The development of a community, especially in terms of social mobility, is influenced by economic, social and cultural capital ownership. Social capital enhances the mobilization of a community's resources and thus promotes a sense of unity among the community. Whereas cultural capital is a productive investment in the economy, being a tool for benefiting other capitals and can be used by individuals to develop actionable strategies which are needed to succeed in a competitive world. The objective of this article are to discusses the social capital ownership patterns based on the networking and trust structure among the community, as well as cultural capital ownership patterns and their influence on the lives and well-being of the settler community. The survey was conducted on 1501 respondents using a purposive sampling and multi-stages method. The findings of this study suggest that FELDA needs to implement and design programs that will strengthen the future planning of the FELDA community and further strengthen the relationship among the settlers to enhance their social and cultural capital along with their economic capital. Research on the construction and empowerment of economic, social and cultural capital is essential in addressing the needs of the poor community for them to participate effectively in the changing of national and global economic dynamic.